A review on health benefits of kombucha nutritional compounds and metabolites. Issue 1 (1st January 2018) - Martínez Leal, Jessica; Valenzuela Suárez, Lucía; Jayabalan, Rasu; Huerta Oros, Joselina; Escalante-Aburto, Anayansi
ABSTRACT: Kombucha is a beverage made by fermenting sugared tea using a symbiotic culture of bacteria and yeasts. Kombucha consumption has been associated with some health effects such as: the reduction of cholesterol levels and blood pressure, reduction of cancer propagation, the improvement of liver, the immune system, and gastrointestinal functions. The beneficial effects of kombucha are attributed to the presence of bioactive compounds that act synergistically. Bacteria contained in kombucha beverage belongs to the genus Acetobacter, Gluconobacter, and the yeasts of the genus Saccharomyces along with glucuronic acid, contribute to health protection. This review focuses on recent findings regarding beneficial effects of kombucha and discusses its chemical compounds, as well as the metabolites resulted by the fermentation process. Besides, some contraindications of kombucha consumption are also reviewed.